Manajemen Keuangan dan Pemasaran UMKM Dalam Perspektif Islam Sebagai Upaya Menekan Angka Kemiskinan - Novi Yanti Sandra Dewi (ITB AAS INDONESIA Surakarta, 2023)
The poverty rate has increased in several regions in Indonesia, including in West Lombok Regency, West Nusa Tenggara. Efforts to reduce the rate of increase in the poverty rate must be continued. One of them is by encouraging the real sector through UMKM. This research was conducted to determine the financial management and marketing of UMKM in accordance with Islamic teachings. This research is qualitative research with data collection techniques using primary and secondary data. Interviews were conducted with micro-scale mushroom business actors using a purposive procedure. Data analysis techniques used the phenomenological method and tested the validity of the triangulation of researchers, methods, theories and data sources. UMKM in West Lombok Regency have not implemented the two principles of Islamic business to the fullest. The two principles are the principle of justice and the principle of benefit. This makes the goal of the existence of Islamic sharia not to be realized optimally, namely human welfare, one of which is realized by avoiding people from misery or poverty in the world. The research is expected to contribute to the development of UMKM, especially in West Lombok Regency so that it can reduce poverty.